Rates of adverse events and correction procedures after elective versus emergent aortouni-iliac endografting during mid-term follow-up: A prospective cohort study. (June 2015) - Prusa, Alexander M.; Nolz, Richard; Wibmer, Andreas G.; Schoder, Maria; Teufelsbauer, Harald
Abstract: Background: Due to preferential implantation of bifurcated devices during endovascular repair of infrarenal abdominal aortic aneurysms (AAA), longer-term results following aortouni-iliac (AUI) endografting are scarce. The aim of this study was to determine the rate of endoleaks as well as frequency of secondary correction procedures after elective and emergent AUI endografting. Methods: A prospectively gathered database at a tertiary care university hospital was retrospectively reviewed from January 2000 until January 2012. This interrogation identified 61 patients who had undergone AUI endografting to treat their AAA. Data retrieval obtained 47 patients with elective AAA repairs while 14 patients received emergent AUI endografting in case of rupture. Procedural outcomes, endoleaks, complications, and secondary interventions during mid-term follow-up were recorded for analysis. Results: Fifty-five patients of the study cohort were male (90.2%) and mean age was 76.5 years (median: 77.2, Q1–Q3: 72.1–81.6). Patient demographics, comorbidities, procedural characteristics, as well as median follow-up length (39.8 months versus 34.9 months) were similar between groups. Endoleaks, complications, and rate of secondary correction procedures were not increased following emergent AUI endografting. The majority of these interventions comprised catheter-based or less invasive surgical procedures. All patients requiring major surgery (three open surgical conversions with endograft explantation and one open aortic banding) survived, while one patient sustained fatal myocardial infarction after a transluminal correction procedure. Conclusion: Emergent AUI endografting was not associated with higher rates of adverse events or correction procedures during mid-term follow-up. Secondary interventions to maintain aneurysm exclusion could be carried out with low mortality. Highlights: Longer-term results following aortouni-iliac (AUI) endografting of infrarenal abdominal aortic aneurysms are scarce. The aim was to determine the rate of adverse events and secondary procedures after elective and emergent AUI endografting. Emergent AUI endografting was not associated with higher rates of adverse events during mid-term follow-up. Secondary interventions to maintain aneurysm exclusion could be carried out with low mortality.